Los elementos naturales y sociales de nuestra localidad - Aguirre Zaquinaula, Enma Angela (2019)
The work of professional sufficiency entitled: The natural and social elements of the locality is in the area of Social Personnel, the assigned competence was: Responsibly manages the space and the environment, with its capacity includes the relationships between natural elements and social; its performance describes the urban and rural geographical spaces of its locality and region and a protected natural area, recognizes the relationship between the natural and social elements that compose them._x000D_ In the development of the learning session, the pedagogical and didactic processes were applied, as well as the learning strategies that encouraged reflexive critical thinking to interpret the relationships of the natural and social elements of their locality, as well as to guide students to make decisions or make possible commitments to make and fulfill with respect to the care of natural and social elements their environment.